Clinical presentation, management and outcomes of bile duct injuries after laparoscopic cholecystectomy: a 15-year single-center experience in Vietnam - Vu, Hung Quang; Quach, Duc Trong; Nguyen, Bac Hoang; Le, Anh-Tuan Quan; Le, Nhan Quang; Pham, Hai Minh; Tran, Ngoc-Huy Thai; Nguyen, Dang-Khoa Hang; Duong, Ngoc-Sang Thi; Tran, Toan Van; Pham, Binh Long (Frontiers in Surgery, 2023)
Objectives: To evaluate the clinical presentation, management, and outcomes of bile duct injuries (BDIs) after laparoscopic cholecystectomy (LC).Methods: This is a case series of 28 patients with BDIs after LC treated at a tertiary hospital in Vietnam during the 2006-2021 period. The BDI's clinical presentations, Strasberg classification types, management methods, and outcomes were reported.Results: BDIs were diagnosed intraoperatively in 3 (10.7%) patients and postoperatively in 25 (89.3%). The BDI types included Strasberg A (13, 46.4%), D (1, 3.6%), E1 (1, 3.6%), E2 (4, 14.3%), E3 (5, 17.9%), D+E2 (2, 7.1%), and nonclassified (2, 7.1%). Of the postoperative BDIs, the injury manifested as biliary obstruction (18, 72.0%), bile leak (5, 20.0%), and mixed scenarios (2, 8.0%). Regarding diagnostic methods, endoscopic retrograde cholangiopancreatography (ERCP) was more useful in bile leak scenarios, while multislice computed tomography, magnetic resonance cholangiopancreatography, and percutaneous transhepatic cholangiography were more useful in biliary obstruction scenarios. All 28 BDIs were successfully treated. ERCP with stenting was very effective in the majority of Strasberg A BDIs. For more complex BDI types, hepaticocutaneous jejunostomy was a safe and effective approach. The in-hospital morbidities included postoperative pneumonia (2, 10.7%) and biliary-enteric anastomosis leakage (1, 5.4%).There was no cholangitis or anastomotic stenosis during the follow-up after discharge (median 18 months).The majority of BDIs were type A and diagnosed postoperatively. ERCP was effective for the majority of Strasberg A BDIs. For major and complex BDIs, hepaticocutaneous jejunostomy is a safe and effective approach.